The Modeling of Effect of Selected Personal and Occupational Characteristics on Burnout of Sports Massagers in Tehran - Mohsen Hallaji; Ahmad Mahmoudi; Esmaeil Madani (Archives in Sport Management and Leadership)
The purpose of this study was to determine the effect of selected personal and occupational factors with burnout dimensions of sports massage therapists in Tehran. This research is descriptive-explanatory, is applied and data collection is by survey. The statistical population of the study, included all male and female massagers in Tehran, 3,200. Available non-probability sampling method was used to determine the statistical sample. The statistical sample size was determined to be 345 according to Morgan table. The Individual and Occupational Factors Questionnaire (researcher-made) and the Job Burnout Reliability Questionnaire with 0.85 (Maslach et al., 1986) were used as research tools. To analyze the data, descriptive and inferential statistics were used (SPSS 21 software and LISREL 8.8 software was used). The results showed that there is a positive and significant relationship between a selection of personal factors including interest in massage, gender and marriage with job burnout, and there is a negative and significant relationship between work experience and job burnout. The results showed that there is a positive and significant relationship between a selection of job factors, including job satisfaction, the physical environment of the workplace, and shift work, with job burnout. It can be concluded that sport massagers have low job burnout. In general, in all aspects of job burnout, women are better than men.